Corporate Governance and Firm Valuation in Colombia - Carlos Pombo; Luis H. Gutiérrez (Inter-American Development Bank, Research Department, 2007)
This paper studies the separation of ownership and control of 108 listed companies in Colombia from 1996 to 2002, finding that voting rights are greater than cash flow rights because of indirect ownership across firms. The paper also examines the association of various ownership and control measures and separation ratios with a firms value and performance for the same sample of companies that traded their stock from 1998 to 2002. Large blockholders were found to exert a positive influence upon a firms valuation and performance, which validates the positive monitoring approach of large shareholders, but this relationship is not monotonic. The paper further reports results from a 2004 survey which suggests that Colombian firms have been slow to improve their corporate governance practices. – – En este trabajo se analiza la separación de la propiedad y el control de 108 empresas inscritas en bolsa en Colombia entre 1996 y 2002, y se descubre que los derechos de voto son mayores que los derechos referentes al flujo de caja debido a la propiedad indirecta entre empresas. También se analiza la relación de varias medidas de propiedad y control y las proporciones de separación con el valor y el desempe\~no de una empresa para la misma muestra de compa\~nías que cotizaron sus acciones en bolsa entre 1998 y 2002. Se descubre que los tenedores de grandes bloques de acciones ejercen una influencia positiva en la valoración y el desempe\~no de una empresa. El trabajo además da cuenta de resultados de una encuesta efectuada en 2004 que sugiere que las empresas colombianas han mostrado cierta lentitud en el mejoramiento de sus prácticas de buena gestión empresarial.
Keywords: 330